2022
DOI: 10.1002/rmv.2359
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in SARS‐CoV‐2 vaccines: A systematic review of the current studies

Abstract: Designing and manufacturing efficient vaccines against coronavirus disease 2019 (COVID‐19) is a major objective. In this systematic review, we aimed to evaluate the most important vaccines under construction worldwide, their efficiencies and clinical results in healthy individuals and in those with specific underlying diseases. We conducted a comprehensive search in PubMed, Scopus, EMBASE, and Web of Sciences by 1 December 2021 to identify published research studies. The inclusion criteria were publications th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 181 publications
2
27
0
Order By: Relevance
“…Three studies (45-47) met the inclusion criteria; however, they used the same patient databases, hence, overlapping considerably with the included studies from Hong Kong. Lastly, four overlapping studies reported the data retrieved from the Vaccine Adverse Event Reporting System (VAERS) database, of which one (48) was included with the highest quality score, and the remainder were excluded (29, 49, 50). Similarly, three overlapping studies used the data obtained from the WHO VigiBase database, two of which were excluded (51, 52).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (45-47) met the inclusion criteria; however, they used the same patient databases, hence, overlapping considerably with the included studies from Hong Kong. Lastly, four overlapping studies reported the data retrieved from the Vaccine Adverse Event Reporting System (VAERS) database, of which one (48) was included with the highest quality score, and the remainder were excluded (29, 49, 50). Similarly, three overlapping studies used the data obtained from the WHO VigiBase database, two of which were excluded (51, 52).…”
Section: Resultsmentioning
confidence: 99%
“…In vaccinated and unvaccinated populations, vaccine efficacy is assessed by three primary endpoints, including the proportion of recorded infections, symptomatic infections, and severely hospitalized cases ( 43 ). Meanwhile, the titers of RBD-specific IgG, neutralizing antibodies, and T cytokine levels (especially the IFN-γ levels) are adopted as the indicators to determine whether the vaccine induced an effective humoral and cellular immune response in the host ( 44 ). The effectiveness of COVID-19 vaccines has been evaluated in healthy adults ( 45 ), immunocompromised patients ( 46 ), adolescents and children ( 47 , 48 ), pregnant women ( 49 ), and cancer patients ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the infection of HSV-1, an increased incidence rate has been noticed during the coronavirus infectious disease 2019 (COVID-19) pandemic. Several recent studies have discussed the potential causal relationship between vaccination or COVID-19 infection with BP [11][12][13].…”
Section: Etiology Of Bell's Palsymentioning
confidence: 99%
“…Along with a higher risk of developing BP with COVID-19 infection, BP has also been recognized as a common adverse event after COVID-19 vaccination. A systematic review recognized BP as one of the most common adverse events after mRNA and viral vector-based immunization [13]. In addition, a study in Hong Kong reported a significantly increased risk of Bell's palsy following the vaccination of inactivated SARS-CoV-2 vaccine but not the mRNA vaccine [22].…”
Section: Relationship Between Covid-19 and Bell's Palsymentioning
confidence: 99%